Study protocol for the development and pilot-testing of a Self-assessment tool for the implementation of the European Standards of Care for Newborn Health (ESCNH) - James Webbe; Helmut Hummler; Luc J I Zimmermann; Ylva Thernström Blomqvist; Nicholas Lack; Dietmar Schlembach; Julia Hoffmann; Silke Mader; Eleni Vavouraki; Sarah Lehmann; Gina Ancora; Esther Schouten; et al. (BMJ Paediatrics Open)
Introduction In Europe, disparities exist in having access to optimal neonatal care. With the European Standards of Care for Newborn Health (ESCNH), evidence-based reference standards are available which provide guidance to improve the care for preterm and ill newborns. To support healthcare professionals (HCPs) and hospital/clinic management in identifying the extent of ESCNH implementation, a feasible assessment tool is required. Such a tool should help identify areas in need of improvement and provide clear recommendations for action. We aim to develop a digital self-assessment tool for HCPs to detect the local level of ESCNH fulfilment and identify areas in need of improvement, and thus provide recommendations for action.Methods and analysis The self-assessment tool will have the form of a digital questionnaire with condensed ESCNH content. A Project Expert Group provides scientific input. With pretesting among HCPs, a template of a questionnaire section is evaluated and adapted accordingly. The subsequently developed full questionnaire will be appraised within a two-round eDelphi survey by at least 50 invited HCPs. Statements and formulations need to be accepted by at least 80% of participants. The remaining discrepancies will be solved in a final workshop. The resulting digital self-assessment tool (SAT) will be translated into several languages and evaluated in a pilot-testing among at least 20 hospitals/clinics across Europe.Conclusion With the self-reflection through the SAT, HCPs, hospital/clinic managers, policymakers and other stakeholders will receive feedback on the conformity with the ESCNH and guidance for improvement.Trial registration number NCT06379828.